Night shift work and chronic lymphocytic leukemia in the MCC‐Spain case–control study. Issue 9 (27th July 2016) - Costas, Laura; Benavente, Yolanda; Olmedo‐Requena, Rocío; Casabonne, Delphine; Robles, Claudia; Gonzalez‐Barca, Eva‐Maria; de la Banda, Esmeralda; Alonso, Esther; Aymerich, Marta; Tardón, Adonina; Marcos‐Gragera, Rafael; Gimeno‐Vázquez, Eva; et al.
Abstract : Chronic lymphocytic leukemia (CLL) has few known modifiable risk factors. Recently, circadian disruption has been proposed as a potential contributor to lymphoid neoplasms' etiology. Serum melatonin levels have been found to be significantly lower in CLL subjects compared with healthy controls, and also, CLL prognosis has been related to alterations in the circadian molecular signaling. We performed the first investigation of an association between night shift work and CLL in 321 incident CLL cases and 1728 population‐based controls in five areas of Spain. Participants were interviewed face‐to‐face by trained interviewers to collect information on sociodemographic factors, familial, medical and occupational history, including work shifts and other lifestyle factors. We used logistic regression models adjusted for potential confounders to estimate odds ratios (OR) and 95% confidence intervals (CI). Seventy‐nine cases (25%) and 339 controls (20%) had performed night work. Overall, working in night shifts was not associated with CLL (OR = 1.06; 95% CI = 0.78–1.45, compared with day work). However, long‐term night shift (>20 years) was positively associated with CLL (OR(tertile 3 vs . day‐work)  = 1.77; 95% = 1.14–2.74), although no linear trend was observed ( P trend = 0.18). This association was observed among those with rotating (OR(tertile 3 vs . day‐work)  = 2.29; 95% CI = 1.33–3.92; P t rend = 0.07), but not permanent night shifts (OR(tertile 3 vs . day‐work) = 1.16; 95% CI = 0.60–2.25; P trend = 0.86). The association between CLL and long‐term rotating night shift warrants further investigation. Abstract : What's new? Patients with chronic lymphocytic leukemia (CLL) exhibit significant reductions in serum melatonin and alterations in circadian molecular signaling, suggesting that circadian disruption has a role in CLL etiology. In this study of CLL patients in Spain, the authors found that long‐term night shift work was associated with an increased risk of CLL, particularly among persons with rotating shift schedules. CLL risk did not increase linearly, however, with years of exposure. Further study of the influence of night shift work on CLL risk could advance understanding of CLL etiology and help informing public health decisions.